Validity of a two-component imaging-derived disease activity score for improved assessment of synovitis in early rheumatoid arthritis. (1st March 2019) - Hensor, Elizabeth M A; McKeigue, Paul; Ling, Stephanie F; Colombo, Marco; Barrett, Jennifer H; Nam, Jackie L; Freeston, Jane; Buch, Maya H; Spiliopoulou, Athina; Agakov, Felix; Kelly, Stephen; Lewis, Myles J; et al.
Abstract: Objectives: Imaging of joint inflammation provides a standard against which to derive an updated DAS for RA. Our objectives were to develop and validate a DAS based on reweighting the DAS28 components to maximize association with US-assessed synovitis. Methods: Early RA patients from two observational cohorts ( n = 434 and n = 117) and a clinical trial ( n = 59) were assessed at intervals up to 104 weeks from baseline; all US scans were within 1 week of clinical exam. There were 899, 163 and 183 visits in each cohort. Associations of combined US grey scale and power Doppler scores (GSPD) with 28 tender joint count and 28 swollen joint count (SJC28), CRP, ESR and general health visual analogue scale were examined in linear mixed model regressions. Cross-validation evaluated model predictive ability. Coefficients learned from training data defined a re-weighted DAS28 that was validated against radiographic progression in independent data (3037 observations; 717 patients). Results: Of the conventional DAS28 components only SJC28 and CRP were associated with GSPD in all three development cohorts. A two-component model including SJC28 and CRP outperformed a four-component model ( R 2 = 0.235, 0.392, 0.380 vs 0.232, 0.380, 0.375, respectively). The re-weighted two-component DAS28CRP outperformed conventional DAS28 definitions in predicting GSPD (Δtest log-likelihood <−2.6, P < 0.01), Larsen score and presence of erosions. Conclusion: A score based on SJC28 and CRP alone demonstrated stronger associations with synovitis and radiographic progression than the original DAS28 and should be considered in research on pathophysiological manifestations of early RA. Implications for clinical management of RA remain to be established.